Fatal haematemesis arising from benign oesophagoatrial fistula. Issue 9 (September 1988) - Zeiderman, M R; O'Grady, J T
Abstract : An 86 year old woman with a Barrett's oesophagus, a benign oesophageal stricture, and a benign ulcer developed an oesophagoatrial fistula. As in previously reported cases, she died after a massive haematemesis.